#### Answer

$y=\sqrt[4]{-x}+1$

#### Work Step by Step

We begin with:
$f(x)=\sqrt[4]{x}$
We are told to reflect in the $y$-axis and shift up 1 unit. This means: $y=f(-x)+1$. Thus we get:
$y=\sqrt[4]{-x}+1$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$y=\sqrt[4]{-x}+1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.